From Proposal to Manuscript: How Constructivist Pedagogy Improves Research Proposal Writing among EFL Undergraduates - Ismail; Arismunandar; Abdul Haling (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study investigates how constructivist pedagogy enhances the research proposal and manuscript writing competence of English as a Foreign Language (EFL) undergraduates. Responding to the challenges of low academic writing quality and limited publication outcomes in Indonesian higher education, the study implemented a twelve-week constructivist intervention integrating guided inquiry, peer collaboration, project-based learning, and reflective practice. A mixed-method quasi-experimental design was employed, combining quantitative (pretest–posttest) and qualitative (reflective journals and interviews) data. Participants comprised 22 students enrolled in a Research Proposal Writing course at Universitas Muhammadiyah Enrekang. Quantitative results revealed a statistically significant improvement across all five writing dimensions—Conceptual Clarity, Argument Development, Methodological Coherence, Language Accuracy, and Organization—with a large effect size (Cohen’s d = 2.18). Students’ writing self-efficacy also increased substantially in cognitive, linguistic, and regulative domains (p < .001), reflecting enhanced confidence, autonomy, and reflective awareness. Thematic analysis of qualitative data identified four major patterns of growth: (1) deepened understanding of research logic, (2) increased collaborative engagement, (3) development of reflective and self-regulated learning, and (4) shift from dependence to autonomy. The integration of both data strands confirms that constructivist pedagogy improves not only writing performance but also higher-order cognitive and affective capacities, enabling students to view writing as a process of inquiry rather than a static product. The findings extend constructivist learning theory within EFL contexts and provide an instructional model for fostering academic literacy and research competence aligned with Sustainable Development Goal 4 (Quality Education).